Autovacinas: técnicas de preparo e fatores de eficiência Autogenous vaccine: preparation technique and efficiency factors - Rolando Cury (Universidade de São Paulo, 1972)
Verificou-se que a obtenção de excelentes autovacinas é possível usando-se a técnica de semeadura, dos germes apropriados, isolados de um material clínico em meios de cultura selecionados. As condições do cultivo devem ser adequadas para estimular, ou pelo menos preservar, as qualidades antigênicas dos germes. O processo de inativação necessita ser cuidadosamente acertado, a fim de não lesar os antígenos presentes. Foram descritos métodos capazes de cumprir estes requisitos, e que ao mesmo tempo fossem práticos e relativamente simples em sua execução, com equipamentos ao alcance de qualquer laboratório clínico. A very good autogenous vaccine may be obtained by inoculation, in a separate medium, of microorganisms collected from clinical material. A selected culture medium and adequate culture conditions are necessary to stimulate or at least preserve the antigenic properties of microorganisms. The inactivation process must be used carefully in order to prevent damage to existing antigenous contents of the bacteria. A description of a method capable of covering every requirement and which would at the same time be practical and of a relatively simple execution, with the equipment available in any clinical laboratory was attempted in this study. This method has been selected from the best present knowledge of bacteriological technique. It is not considered beyond improvement, in part or in whole, as new and better knowledge is added to Immunology and Bacteriology.